PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN STRESS KERJA TERHADAP KINERJA KARYAWAN PT KILANG PERTAMINA BALIKPAPAN - Retta Hutahayan, Claudya; Hernadi Moorcy, Nadi (MEDIA RISET EKONOMI [MR.EKO], 2026)
The purpose of this study was to determine The Effect of Workload, Work Environment, and Job Stress on Employee Performance. The data used is an existing source of both internal and external data and the data can be accessed through the internet and is readily available to the public information. Data analysis methods were used the Validity Test, Reliability Test, Classical Assumption Test, and t-Test. The results of the analysis show that the Workload variable has a significant effect on Employee Performance. Work Environment Variables have a significant effect on Employee Performance. Variable Job Stress has a significant effect on Employee Performance as well as the most dominant element on Employee Performance. Keywords: Workload, Work Environment, Job Stress, and Employee Performance